Next-Generation Sequencing Identifies Extended HLA Class I and II Haplotypes Associated With Early-Onset and Late-Onset Myasthenia Gravis in Italian, Norwegian, and Swedish Populations - Creary, Lisa E.; Gangavarapu, Sridevi; Caillier, Stacy J.; Cavalcante, Paola; Frangiamore, Rita; Lie, Benedicte A.; Bengtsson, Mats; Harbo, Hanne Flinstad; Brauner, Susanna; Hollenbach, Jill A.; Oksenberg, Jorge R.; Bernasconi, Pia; et al. (Frontiers in Immunology, 2021)
Genetic susceptibility to myasthenia gravis (MG) associates with specific HLA alleles and haplotypes at the class I and II regions in various populations. Previous studies have only examined alleles at a limited number of HLA loci that defined only broad serotypes or alleles defined at the protein sequence level. Consequently, genetic variants in noncoding and untranslated HLA gene segments have not been fully explored but could also be important determinants for MG. To gain further insight into the role of HLA in MG, we applied next-generation sequencing to analyze sequence variation at eleven HLA genes in early-onset (EO) and late-onset (LO) non-thymomatous MG patients positive for the acetylcholine receptor (AChR) antibodies and ethnically matched controls from Italy, Norway, and Sweden. For all three populations, alleles and haplotype blocks present on the ancestral haplotype AH8.1 were associated with risk in AChR-EOMG patients. HLA-B*08:01:01:01 was the dominant risk allele in Italians (OR = 3.28, P = 1.83E-05), Norwegians (OR = 3.52, P = 4.41E-16), and Swedes (OR = 4.24, P<2.22E-16). Protective alleles and haplotype blocks were identified on the HLA-DRB7, and HLA-DRB13.1 class II haplotypes in Italians and Norwegians, whereas in Swedes HLA-DRB7 exhibited the main protective effect. For AChR-LOMG patients, the HLA-DRB15.1 haplotype and associated alleles were significantly associated with susceptibility in all groups. The HLA-DR13~HLA-DR~HLA-DQ haplotype was associated with protection in all AChR-LOMG groups. This study has confirmed and extended previous findings that the immunogenetic predisposition profiles for EOMG and LOMG are distinct. In addition, the results are consistent with a role for non-coding HLA genetic variants in the pathogenesis of MG.